Increased Intracranial Pressure during Hemodialysis in a Patient with Anoxic Brain Injury. (20th March 2017) - Lund, Anton; Damholt, Mette B.; Strange, Ditte G.; Kelsen, Jesper; Møller-Sørensen, Hasse; Møller, Kirsten
Abstract : Dialysis disequilibrium syndrome (DDS) is a serious neurological complication of hemodialysis, and patients with acute brain injury are at increased risk. We report a case of DDS leading to intracranial hypertension in a patient with anoxic brain injury and discuss the subsequent dialysis strategy. A 13-year-old girl was admitted after prolonged resuscitation from cardiac arrest. Computed tomography (CT) revealed an inferior vena cava aneurysm and multiple pulmonary emboli as the likely cause. An intracranial pressure (ICP) monitor was inserted, and, on day 3, continuous renal replacement therapy (CRRT) was initiated due to acute kidney injury, during which the patient developed severe intracranial hypertension. CT of the brain showed diffuse cerebral edema. CRRT was discontinued, sedation was increased, and hypertonic saline was administered, upon which ICP normalized. Due to persistent hyperkalemia and overhydration, ultrafiltration and intermittent hemodialysis were performed separately on day 4 with a small dialyzer, low blood and dialysate flow, and high dialysate sodium content. During subsequent treatments, isolated ultrafiltration was well tolerated, whereas hemodialysis was associated with increased ICP necessitating frequent pauses or early cessation of dialysis. In patients at risk of DDS, hemodialysis should be performed with utmost care and continuous monitoring of ICP should be considered.